SGLT2 inhibitor treatment is not associated with an increased risk of osteoporotic fractures when compared to GLP-1 receptor agonists: A nationwide cohort study - Al-Mashhadi, Zheer Kejlberg; Viggers, Rikke; Starup-Linde, Jakob; Vestergaard, Peter; Gregersen, Søren (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes mellitus (T2D) is associated with an increased fracture risk. It is debated whether sodium-glucose cotransporter 2 (SGLT2) inhibitors influence fracture risk in T2D. We aimed to investigate the risk of major osteoporotic fractures (MOF) with SGLT2 inhibitors compared to glucagon-like peptide 1 (GLP-1) receptor agonists when used as add-on therapies to metformin. Methods: We conducted a population-based cohort study using Danish national health registries. Diagnoses were obtained from discharge diagnosis codes (ICD-10 and ICD-8-system) from the Danish National Patient Registry, and all redeemed drug prescriptions were obtained from the Danish National Prescription Registry (ATC classification system). Subjects treated with metformin in combination with either SGLT2 inhibitors or GLP-1 receptor agonists were identified and enrolled from 2012 to 2018. Subjects were then propensity-score matched 1:1 based on age, sex, and index date. Major osteoporotic fractures (MOF) were defined as hip, vertebral, humerus, or forearm fractures. A Cox proportional hazards model was utilized to estimate hazard rate ratios (HR) for MOF, and survival curves were plotted using the Kaplan-Meier estimator. Results: In total, 27,543 individuals treated with either combination were identified and included. After matching, 18,390 individuals were included in the main analysis (9,190 in each group). Median follow-up times were 355 [interquartile range (IQR) 126-780] and 372 [IQR 136-766] days in the SGLT2 inhibitor and GLP-1 receptor agonist group, respectively. We found a crude HR of 0.77 [95% CI 0.56-1.04] for MOF with SGLT2 inhibitors compared to GLP-1 receptor agonists. In the fully adjusted model, we obtained an unaltered HR of 0.77 [95% CI 0.56-1.05]. Results were similar across subgroup- and sensitivity analyses. Conclusion: These results suggest that SGLT2 inhibitors have no effect on fracture risk when compared to GLP-1 receptor agonists. This is in line with results from previous studies.